The Effect of Halal Certification, Halal Awareness and Product Knowledge on Purchase Decisions for Halal Fashion Products - Afendi, Arif (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
In this modern era, many companies produce fashion products labeled halal to increase sales value and increase public awareness about the importance of buying products tagged halal according to religious law. This study aims to examine the effect of halal certification, halal awareness and product knowledge on purchasing decisions for halal fashion products and provide a perspective on the importance of using halal products in society. This article type of research is quantitative; this journal's research data were obtained from 100 respondents who used halal fashion products in Semarang. The research data were analyzed using multiple linear regression. This article's research shows that halal certification has a positive but insignificant effect on fashion products' purchasing decisions labeled halal. Halal awareness has a positive and significant impact on product purchasing decisions. Product knowledge also has a positive and significant effect on purchasing decisions.